Is the Economic Convergence of the Mexican States Possible? Estimates for the 1940-2013 Period - Mario Camberos C., Mario Camberos C.; Bracamontes N., Joaquín (Journal of Reviews on Global Economics, 2016)
In this paper we study β-convergence: absolute and conditional, also sigma convergence, using cross-state regression models, based in a long term period of time for the Federated States of Mexico. When absolute convergence is estimated (Solow Model, 1956) we found the negative sign expected but the result is not statistically reliable; while, estimates for decades only show absolute convergence for the period of 1960-1970, known with the term of "Mexican Miracle", a third regression including population growth rate and physical capital investment per capita, variables as considered by Solow models, confirm that there is not absolute convergence like the first result obtained. The estimate including human capital index (HCI) and human development index (HDI 2), shows a number of outliers, suggesting the introduction of proxy variables which capture the political effects and explore conditional convergence. When panel heteroskedastic is considerate, convergence is observed, but β 2% any case was estimated.